PENERAPAN MODEL PEMBELAJARAN THINK, WRITE, AND TALK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN KEWIRAUSAHAAN - Henny Zurika Lubis (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
This study aims to improve students' activity and learning outcomes through the application of thinking, write, and talk learning models as an effort to improve the quality of learning in entrepreneurship courses. The research method used is classroom action research procedure, with data collection techniques in this study include tests, documentation and further observations of data analysis techniques used in this study in the form of descriptive analysis and qualitative analysis.Based on the results of observational data analysis that the activity of students in the first cycle is still low, and in cycle II, students are already active it is seen an increase in student activity in cycle II of 67% and it will be related to student learning outcomes, A complete cycle I only 40% in cycle II of 63.33% means that the increase in learning outcomes in cycle II compared to the cycle I that the learning outcomes of entrepreneurship cycle II turned out better results, so it can be concluded that entrepreneurial learning by applying the model of learning Think, write, and talk classroom can improve student learning outcomes.Keywords: Think, Write, and Talk Learning Model, Entrepreneurship, Learning, Outcomes